Answer:
A.
1) 5(2x) = 10x
2) 5(2x2) = 10x^2
3) (5x+y)(8xy4) = 40x^2 + 8xy5
B.
1) 5(2x + 3) = 10x+15
2) 5xy(2x + y) = 10x^2y + 5xy^2
3) 5x2y3(8xy4 - 2) = 40x^3y^7 - 10x^2y^3
4). 5x(2x2 - 3x) = 10x^3-15x^2
C.
1) (2x + 3)(3x + 1) = 6x^2 + 11x + 3
2) (2x2 + 3y)(3x2 - y) = 6x^4 +7x^2+y -3y^2
3) (2x2 - 3y)(3x2 - y2) = 6x^4 - 2x^2y^2 -9x^2 +3y^3
D.
1) (3x + 9)(2x + 5y + 4) = 6x^2+15xy+30x+45y+36
2) (3x + 9y)(2x - 5y2 - 4z2) = 6x^2-15xy^2-12xz^2+18xy-45y^3-36yz^2
3) (3x + 9)(2x - 5y + 4z) = 6x^2-15xy+12xz+18x-45y+36z